The Esoteric Ratio of Ecological Verses in the Perspective of Islamic Religious Education: An Interpretative Study of Tafsīr al-Kabīr Mafātīḥ al-Ghayb by Imam al-Rāzī - Sohri Ramdana; Fahrurrozi Fahrurrozi; Iwan Fitriani; Abdullah Fuadi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study explores the esoteric ratio of ecological verses within the framework of Islamic Religious Education by analyzing Imam al-Rāzī’s monumental work, Tafsīr al-Kabīr Mafātīḥ al-Ghayb. The research seeks to uncover how al-Rāzī’s interpretative method integrates rational inquiry with spiritual insight to address ecological themes in the Qur’an, particularly in relation to human responsibility toward nature as a manifestation of divine trust (amānah). Using a qualitative approach with interpretative textual analysis, the study examines selected verses that highlight ecological balance, environmental ethics, and the metaphysical dimensions of creation. The findings reveal that al-Rāzī not only provides a theological explanation of ecological verses but also emphasizes a philosophical-esoteric dimension where nature functions as a sign (āyah) pointing toward divine wisdom. This integration of rationality and esotericism offers a pedagogical implication for Islamic Religious Education by promoting ecological awareness rooted in spiritual values. Furthermore, the study concludes that al-Rāzī’s interpretation presents a holistic model of ecological consciousness, bridging the gap between rational exegesis, esoteric reflection, and contemporary environmental ethics. Such insights are highly relevant to current educational discourse, as they encourage a paradigm that unites faith, reason, and ecological responsibility. In conclusion, this research contributes to the enrichment of Islamic Religious Education by framing ecological issues not merely as environmental concerns but as integral to the spiritual and rational development of learners.